Manufacturing method of powder magnetic core
Patent Information
- Application Number
- JP2020054606
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-03-25
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2040-03-25
AI Technical Summary
【0007】 本開示によれば、より高性能な圧粉磁心が提供される。
Smart Images

Figure 0007637914000001 
Figure 0007637914000002 
Figure 0007637914000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a powder magnetic core used in inductors such as choke coils and transformers. [Background technology]
[0002] In recent years, autonomous driving systems and advanced driver assistance systems have been developed for vehicles. Behind this lies the increase in sensors installed in vehicles and the development of highly integrated circuits such as SoCs (System on Chip) for high-speed processing of the large amounts of information obtained from these sensors. Inductors used in such applications are required to be compact, capable of handling large currents, and have a low DCR.
[0003] As the above-mentioned inductor, for example, a metal composite is known, which is a coil-embedded magnetic element using a dust core produced by compressing a metal magnetic powder. Because the metal composite uses a metal magnetic powder, it has a high saturation magnetic flux density, excellent DC bias characteristics, and can be miniaturized due to its dead-space-less structure. As a dust core used in such a metal composite, Patent Document 1 discloses a composite magnetic material in which a metal magnetic powder is bound with a thermosetting resin. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] US Patent Application Publication No. 2002-0097124 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the above-mentioned conventional composite magnetic materials and the like may not have sufficient performance as a powder magnetic core. In view of the above, an object of the present disclosure is to provide a powder magnetic core with higher performance. [Means for solving the problem]
[0006] A powder magnetic core according to one embodiment of the present disclosure comprises a metal magnetic powder, and a first resin and a second resin having thermosetting properties, wherein the second resin has a higher degree of shrinkage upon heat curing than the first resin, a lower degree of elasticity upon heat curing than the first resin, and a content equal to or less than that of the first resin. Effect of the Invention
[0007] According to the present disclosure, a powder magnetic core with higher performance is provided. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic perspective view showing the configuration of an electrical component including a powder magnetic core according to an embodiment. [Diagram 2] FIG. 2 is an SEM image of the powder magnetic core according to the embodiment. [Diagram 3] FIG. 3 is a flowchart showing a method for producing a powder magnetic core according to an embodiment. [Figure 4] FIG. 4 is a diagram illustrating the effect of adding an epoxy resin according to the embodiment. [Figure 5A] FIG. 5A is a diagram illustrating the effect of the addition of an epoxy resin on magnetic permeability according to the embodiment. [Figure 5B] FIG. 5B is a diagram illustrating the effect on strength with respect to the addition of an epoxy resin according to the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] (Knowledge that led to disclosure) In order to obtain insulation and adhesion between the metal magnetic powder particles, the powdered powder is manufactured by adding an insulating and adhesive resin material to the metal magnetic powder, drying the powder, and then compressing the powdered powder. In order to improve the magnetic properties of the powdered powder core, it is important to reduce the distance between the particles of the metal magnetic powder particles. In other words, it is important to pack the metal magnetic powder densely.
[0010] One of the measures to achieve the above is to increase the pressure during pressure molding. The particles of the metal magnetic powder are pressed against each other in response to the pressure, so the distance between them decreases. Another measure is to reduce the amount of resin material added. Since the total amount of resin material is reduced, less resin material is placed between the particles of the metal magnetic powder on average, and the filling rate of the metal magnetic powder is improved.
[0011] However, although these methods are effective in packing the metal magnetic powder at a high density and obtaining a dust core with high magnetic permeability, the bonds between the particles of the metal magnetic powder are broken, making it easier for cracks to occur (mechanical strength or simply strength is reduced). If the pressure during pressure molding is reduced or the amount of resin material added is reduced in order to suppress the occurrence of cracks, the density of the metal magnetic powder decreases, making it impossible to obtain a dust core with high magnetic properties. In other words, there is a trade-off between the strength and magnetic properties of the dust core.
[0012] According to the present disclosure, by combining two types of resin materials to bond the particles of metal magnetic powder together, it is possible to improve the strength of the powder core while maintaining the magnetic properties, or improve the magnetic properties of the powder core while maintaining the strength, without being dependent on such a trade-off relationship.
[0013] Hereinafter, the embodiment will be specifically described with reference to the drawings.
[0014] Note that the embodiments described below each show a specific example of the present disclosure. The numerical values, shapes, materials, components, component arrangement positions, connection forms, steps, and order of steps shown in the following embodiments are merely examples and are not intended to limit the present disclosure. Furthermore, among the components in the following embodiments, components that are not described in the independent claims are described as optional components.
[0015] (Embodiment) [composition] First, an electrical component as an example of a use of a powder magnetic core according to an embodiment of the present disclosure will be described with reference to Fig. 1. Fig. 1 is a schematic perspective view showing the configuration of an electrical component including a powder magnetic core according to an embodiment. Fig. 1 shows the general shape of a powder magnetic core 10, which will be described later, and further shows the inside of the powder magnetic core 10 in a see-through manner. For example, components such as a coil member 40 that are hidden by being embedded in the powder magnetic core 10 are shown with dashed lines, indicating that they can be seen through the powder magnetic core 10.
[0016] As shown in FIG. 1, the electrical component 100 includes a powder magnetic core 10, a coil member 40, a first terminal member 25, and a second terminal member .
[0017] As one example, the electrical component 100 is a rectangular metal composite, and the approximate outer shape is determined by the shape of the powder core 10. The powder core 10 can be formed into any shape by pressure molding. In other words, the electrical component 100 can be realized in any shape depending on the shape of the powder core 10 during pressure molding.
[0018] More specifically, the electric component 100 is an inductor, and is a passive element that stores the electric energy flowing between the first terminal member 25 and the second terminal member 35 as magnetic energy by the coil member 40. In this embodiment, the electric component 100 is described as one example of use of the powder core 10, but the powder core 10 can simply be used as a magnetic material, and the use example is not limited to the electric component 100 of this embodiment. The powder core 10 may be used for any desired application that can utilize the properties of a magnetic material that has both high magnetic properties (specifically, high magnetic permeability) and high strength.
[0019] Here, Fig. 2 is an SEM observation image of the powder magnetic core according to the embodiment. Fig. 2 shows an image of a cross section of the powder magnetic core 10 observed with a SEM (Scanning Electron Microscope).
[0020] As shown in FIG. 2, the powder magnetic core 10 in this embodiment is composed of metal magnetic powder 11, which is identified as a gray granular object in the figure, a first resin arranged to cover the metal magnetic powder 11, and a second resin present in a scattered manner in the first resin.
[0021] Fe-Si-Al-based, Fe-Si-based, Fe-Si-Cr-based, or Fe-Si-Cr-B-based metal magnetic powder is used as the metal magnetic powder 11. The metal magnetic powder 11 has a higher saturation magnetic flux density than magnetic powders such as ferrite, and is therefore useful when used under high current.
[0022] For example, when Fe-Si-Al-based metal magnetic powder is used, the composition elements are Si 8% to 12% by weight, Al 4% to 6% by weight, and the remaining composition elements are Fe and unavoidable impurities. Here, examples of the unavoidable impurities include Mn, Ni, P, S, and C. By setting the contents of the composition elements constituting the metal magnetic powder 11 within the above composition ranges, high magnetic permeability and low coercive force can be obtained.
[0023] For example, when Fe-Si-based metal magnetic powder is used, the composition elements include Si content of 1% by weight or more and 8% by weight or less, and the remaining composition elements include Fe and unavoidable impurities, which are the same as those described above.
[0024] For example, when Fe-Si-Cr-based metal magnetic powder is used, the composition elements are Si in a range of 1% by weight to 8% by weight, Cr in a range of 2% by weight to 8% by weight, and the remaining composition elements are Fe and unavoidable impurities, which are the same as those described above.
[0025] For example, when Fe-S-Cr-B based magnetic metal powder is used, the composition elements are Si in a range of 1% by weight to 8% by weight, Cr in a range of 2% by weight to 8% by weight, and the remaining composition elements are Fe and unavoidable impurities, which are the same as those described above.
[0026] The role of Si in the composition elements of the above-mentioned metal magnetic powder is to reduce the magnetic anisotropy and magnetostriction constant, increase the electrical resistance, and reduce eddy current loss. By making the Si content in the composition elements 1% by weight or more, it is possible to obtain an improvement effect of soft magnetic properties, and by making it 8% by weight or less, it is possible to suppress the decrease in saturation magnetization and suppress the decrease in DC superposition properties.
[0027] Furthermore, by including Cr in the metal magnetic powder, it is possible to impart an effect of improving weather resistance. By making the Cr content in the composition elements 2% by weight or more, it is possible to obtain an effect of improving weather resistance, and by making it 8% by weight or less, it is possible to suppress the deterioration of soft magnetic properties.
[0028] The average particle diameter of these metal magnetic powders is, for example, 5.0 μm or more and 35 μm or less. From the viewpoint of ensuring voltage resistance, it is preferable to configure the average particle diameter of the metal magnetic powder to be small in order to alleviate electric field concentration between particles, and by setting the average particle diameter as described above, a high filling rate can be ensured. In addition, by setting the average particle diameter of the metal magnetic powder to 35 μm or less, it is possible to reduce core loss in the high frequency range, particularly eddy current loss. The average particle diameter of the metal magnetic powder is measured using a laser diffraction scattering method or the like.
[0029] In this embodiment, the first resin is a silicone resin, and is present, for example, in the locations indicated by the upward white arrows in the figure. The silicone resin is present so as to mainly cover the metal magnetic powder 11, and electrically insulates the particles of the metal magnetic powder 11 from each other.
[0030] On the other hand, the second resin is scattered in places in the first resin covering the metal magnetic powder 11. In this embodiment, the second resin is an epoxy resin, and is present, for example, in places indicated by the downward white arrows in the figure. Since epoxy resin mainly has high strength, its inclusion in the powder core 10 contributes to improving the strength of the powder core 10.
[0031] Thus, the powder magnetic core 10 in this embodiment is composed of two types of thermosetting resin materials. These two types of thermosetting resins are not limited to the combination of silicone resin and epoxy resin, as long as the relationship is satisfied in which the second resin has a higher degree of shrinkage when heat-cured than the first resin and the second resin has a lower degree of elasticity when heat-cured than the first resin. The thermosetting resin used to form the powder magnetic core 10 can be composed using any combination of the first resin and the second resin that satisfies the above relationship. In addition, as the thermosetting resin used in the present invention, it is preferable to select a thermosetting resin whose main agent is liquid at room temperature.
[0032] In addition to the first resin and the second resin, the powder magnetic core 10 may contain a third resin different from the first resin and the second resin, as well as other substances such as an electrical insulating material that strengthens the insulation between particles of the metal magnetic powder.
[0033] 1, the powder magnetic core 10 has rectangular opposing surfaces on which the first terminal member 25 and the second terminal member 35 are respectively formed, and has a substantially quadrangular prism shape with the four sides of each opposing surface connected by a top surface, a bottom surface, and two side surfaces. In this embodiment, the bottom surface and the top surface are rectangular with dimensions of 14.0 mm x 12.5 mm, and the distance from the bottom surface to the top surface is 8.0 mm.
[0034] The coil member 40 is wound with a conductor wire, which is a long conductor covered with an insulating film (winding portion), and both ends of the conductor wire are connected to the first terminal member 25 and the second terminal member 35, respectively (lead portions 20 and 30). In this embodiment, a round conductor wire with a cross-sectional diameter of 0.65 mm is used as the conductor wire. There is no particular limitation on the thickness and shape of the conductor wire, and as long as the thickness allows winding processing, etc., a round conductor wire and a flat conductor wire with a rectangular cross section can be appropriately selected and used. The winding portion is embedded near the center of the powder core 10. In the lead portions 20 and 30, each of the both ends of the conductor wire extends continuously from the winding portion to the opposing surfaces, respectively, and protrudes to the outside of the powder core 10. Here, a part of the lead portion is expanded to have a flat shape and is bent so as to follow the opposing surfaces and the bottom surface. The insulating film covering is peeled off from the expanded portion, making it possible to electrically connect to the outside.
[0035] The first terminal member 25 and the second terminal member 35 are made of a conductive plate such as phosphorus bronze or copper. Each of the first terminal member 25 and the second terminal member 35 has a recess near the center along the opposing surface and is configured to recess into the powder core 10. The lead parts 20 and 30 are disposed outside the recess, and the lead parts 20 and 30 are electrically connected to the first terminal member 25 and the second terminal member 35. The lead parts 20 and 30 are connected to the first terminal member 25 and the second terminal member 35 by resistance welding or the like. The first terminal member 25 and the second terminal member 35 are bent so as to be inserted toward the inside of the powder core 10, and the first terminal member 25 and the second terminal member 35 are fixed to the powder core 10 with the bent parts inserted into the powder core 10.
[0036] Moreover, the first terminal member 25 and the second terminal member 35 are bent together with the lead portions 20 and 30 so as to fit along the bottom surface of the powder core 10. As a result, the lead portions 20 and 30 are routed around the underside of the bottom of the electrical component 100 while being held by the first terminal member 25 and the second terminal member 35. In other words, the lead portions 20 and 30 can be directly connected to lands (not shown) of a mounting board or the like on which the electrical component 100 is mounted.
[0037] It should be noted that the first terminal member 25 and the second terminal member 35 are not essential components. If the lead portions 20 and 30 have the strength to maintain their shape independently, the first terminal member 25 and the second terminal member 35 do not have to be provided.
[0038] [Manufacturing method] Next, a method for manufacturing the above-mentioned powder magnetic core 10 will be described with reference to FIG. 3. FIG. 3 is a flowchart showing a method for manufacturing a powder magnetic core according to an embodiment. In manufacturing the powder magnetic core 10 in this embodiment, first, a metal magnetic substance powder 11 containing predetermined composition elements is prepared (preparation step S101). Next, the metal magnetic substance powder 11 is mixed with an electrical insulating material (not shown). In cases such as when the electrical insulating material is replaced with a resin material to be added later, mixing of the electrical insulating material is not an essential requirement of the embodiment, and this process may be skipped. The thermosetting resin is mixed in a state in which the metal magnetic substance powder 11 and the electrical insulating material are substantially uniformly dispersed by mixing.
[0039] Specifically, first, the first resin is a silicone resin. Dissolve The metal magnetic powder 11 is dissolved in the agent in advance, and then added to the mixture of the metal magnetic powder 11 and the electrical insulating material, and further mixed (kneaded) (first mixing step S102). The metal magnetic powder 11 is coated with the electrical insulating material and silicone resin to electrically insulate each particle from each other.
[0040] Next, the second resin, epoxy resin, is added to the mixture of the metal magnetic powder 11, the electrical insulating material, and the silicone resin in a state where the second resin is dissolved in a solvent such as IPA in advance, and then further mixed (kneaded) (second mixing step S103). The kneading of the thermosetting resin described above is performed by mixing the uncured resin material in a mortar, mixer, or the like. In this embodiment, the ratio of the amount of silicone resin and the amount of epoxy resin added is configured to be 0.08 or more and 1.00 or less in terms of the epoxy resin / silicone resin ratio.
[0041] The mixture is heated at a temperature of 65°C or higher and 150°C or lower to evaporate the solvent, and then pulverized to obtain a composite magnetic material with good moldability. Furthermore, the composite magnetic material is classified to obtain a mixed powder with particle sizes aligned within a specified range, thereby further improving moldability.
[0042] The mixed powder obtained as described above is put into a die and pressure-molded into a desired shape to obtain the powder core 10 (molding step S104). In the molding step S104, a pressure of 3 to 7 ton / cm is applied. 2 Pressure molding is performed within the range.
[0043] As described above, the manufacturing method of powder magnetic core 10 in this embodiment includes a first mixing step S102 of mixing a metal magnetic powder with a first resin before curing that has thermosetting properties, a second mixing step S103 after the first mixing step S102 of mixing a second resin before curing that has thermosetting properties, and a molding step S104 of pressure molding, wherein the second resin has a higher degree of shrinkage when heat-cured than the first resin, a lower degree of elasticity when heat-cured than the first resin, and is contained in an amount equal to or less than the first resin.
[0044] The first resin of the thermosetting resins used in the powder magnetic core 10 is a silicone resin that is both insulating and elastic. After the metal magnetic powder 11 is coated with the first resin, a second resin, an epoxy resin, which is stronger than the first resin, is added in a smaller amount than the first resin. The second resin hardens after a temporary volume expansion. During the volume expansion of the second resin, the second resin softens once and is dispersed and scattered within the first resin.
[0045] Thereafter, the shrinkage rate of the second resin during hardening is greater than that of the first resin, and the distance between each particle of the metal magnetic powder 11 can be reduced during hardening. In this manner, the distance between the particles is small and the particles are densely packed. For this reason, in this embodiment, a dust core 10 having high magnetic permeability and strength can be obtained. The formed dust core 10 is also endowed with heat resistance, which is a characteristic of silicone resin.
[0046] Examples of the powder magnetic core 10 according to the above embodiment will be described in detail below.
[0047] (Example) In the following example, a dust core 10 using Fe-Si-Cr based metal magnetic powder with an average particle size of 10 μm as the metal magnetic powder 11 will be described.
[0048] Metal magnetic powder 100g To On the other hand, a mixed powder was prepared by mixing silicone resin and epoxy resin at the addition ratio shown in Fig. 4. Fig. 4 is a diagram for explaining the effect of adding epoxy resin according to the embodiment.
[0049] The mixed powder was dried at a temperature of 80°C, and then classified to adjust the particle size to a predetermined range. The adjusted mixed powder thus obtained was subjected to 4 ton / cm at room temperature. 2 A ring core having an outer diameter of 14.0 mm, an inner diameter of 10.0 mm, and a thickness of 2.00 mm was produced by pressure molding at a pressure of 1.0 mm. The mixture was then dried at a temperature of 150° C. for 2 hours to harden the thermosetting resin, thereby producing the powder magnetic core 10 of this example.
[0050] [Initial permeability] The initial permeability was calculated by measuring the inductance L at 0 A using an LCR meter, and calculating the initial permeability μi from the following formula 1 (measurement frequency 100 kHz).
[0051] μi = (L × le) / (μ0 × Ae × n 2 ) ···(1)
[0052] Here, le is the effective magnetic path length, μ0 is the magnetic permeability of a vacuum, Ae is the cross-sectional area, and n is the number of turns of the measuring coil.
[0053] [Strength] The strength was measured at 4 ton / cm 2 The pre-cured test specimen was then hardened by drying at a temperature of 150°C for 2 hours to prepare a test specimen.
[0054] The prepared test piece was subjected to a three-point bending test, and a load was applied at a rate of 0.5 mm / min. The load applied when the test piece broke was used as the measured value. The strength σ (N / mm 2 ) was calculated.
[0055] σ=3×Pb×Ls / 1WT 2 (2)
[0056] Here, Pb is the load (measured value) applied when the test piece broke, and Ls is the distance between the supports in mm.
[0057] [result] The test results of each sample prepared in this example will be described with reference to FIG. 4 as well as FIG. 5A and FIG. 5B.
[0058] 5A is a diagram for explaining the effect on magnetic permeability of the addition of an epoxy resin according to the embodiment. FIG. 5B is a diagram for explaining the effect on strength of the addition of an epoxy resin according to the embodiment. The fifth column of FIG. 4 shows the initial magnetic permeability obtained as a result of the above test as magnetic permeability, and the sixth column of FIG. 4 shows the strength [N / mm 2 4. Also, corresponding to the fifth column of FIG. 4, FIG. 5A shows a graph plotting the magnetic permeability of the specimen against the additive rate of the epoxy resin. Also, corresponding to the sixth column of FIG. 4, FIG. 5B shows a graph plotting the strength of the specimen against the additive rate of the epoxy resin. In addition to the specimen number, the first column of FIG. 4 has "*" added to distinguish the comparative example. For example, the specimen with specimen number 1 indicates that it is a specimen related to the comparative example with "*" added.
[0059] As shown in the samples of sample numbers 1 to 3 in FIG. 4, in samples containing only silicone resin as the thermosetting resin, the magnetic permeability decreases as the amount of added thermosetting resin increases.
[0060] On the other hand, as shown in the specimens Nos. 4 to 10 in Fig. 4, and Figs. 5A and 5B, in specimens in which epoxy resin was added in addition to silicone resin as a thermosetting resin, strength increased according to the amount of epoxy resin added, compared to specimen No. 2, and furthermore, the magnetic permeability increased temporarily, peaking at specimen No. 8. Also, it can be seen that specimen No. 10 is a specimen with significantly higher strength while maintaining the same magnetic permeability, compared to specimen No. 3, which has a lower total amount of thermosetting resin added (i.e., silicone resin + epoxy resin).
[0061] This result is due to the fact that by adding epoxy resin after the metal magnetic powder 11 is coated with silicone resin, the epoxy resin becomes softened when it cures and shrinks, causing the epoxy resin to be present in a scattered form in the silicone resin. Since the cure shrinkage rate of the scattered epoxy resin is greater than that of the silicone resin, the distance between each particle of the metal magnetic powder 11 can be reduced during the curing process, resulting in a greater magnetic permeability. At the same time, a dust core 10 can be obtained that has both the high strength property of the epoxy resin and the high heat resistance property of the silicone resin.
[0062] If the ratio of the silicone resin to the epoxy resin is 1 or more in terms of the epoxy resin / silicone resin ratio, the effect of the epoxy resin becomes dominant in forming gaps between the metal magnetic powder, and the magnetic permeability decreases. Therefore, it is preferable that the content of the second resin is equal to or less than that of the first resin. In this way, simply constructing a powder core containing a large amount of epoxy resin will only result in a powder core with low magnetic permeability, and there is an appropriate range for the amount of epoxy resin added.
[0063] For example, sample number 4 contains 3.00% by weight of silicone resin and 0.25% by weight of epoxy resin. weight% and processing. In the cross-sectional SEM image of the specimen obtained as a result, the area occupancy rate of the epoxy resin is 2.28%, the area occupancy rate of the metal magnetic powder is 65.95%, and the area occupancy rate of the silicone resin is 31.77%. Therefore, the area ratio of the epoxy resin to the silicone resin in the specimen after preparation is 2.28 / 31.77=0.07.
[0064] Similarly, sample number 10 contained 3.00% by weight of silicone resin and 3.00% by weight of epoxy resin. weight % and processed. In the SEM observation image of the cross section of the specimen obtained as a result, the area occupancy of the epoxy resin is 19.62%, the area occupancy of the metal magnetic powder is 58.36%, and the area occupancy of the silicone resin is 22.02%. Therefore, the area ratio of the epoxy resin to the silicone resin in the specimen after preparation is 19.62 / 22.02=0.89. That is, the area occupancy of the second resin in the cross section is effective when it is contained in at least a small amount, and exists in a range of 19.62% (i.e., 20%) or less. In other words, the area occupancy of the second resin in the cross section may be greater than 0.0% and less than 20%. In addition, the area ratio of the second resin to the first resin in the cross section is greater than 0.07 or more, and less than 0.9, 0.89 or less. In other words, the area ratio of the second resin to the first resin in the cross section may be greater than 0.0 and less than 0.9.
[0065] [Effects, etc.] As described above, the powder magnetic core 10 according to this embodiment comprises a metal magnetic powder 11, and a first resin and a second resin having thermosetting properties, the second resin having a higher degree of shrinkage upon thermosetting than the first resin, a lower degree of elasticity upon thermosetting than the first resin, and a content equal to or less than that of the first resin.
[0066] In such a powder core 10, the second resin, which is dispersed in the first resin, brings the particles of the metal magnetic powder 11 into close proximity with each other when it hardens and shrinks, improving the magnetic permeability of the entire powder core 10. In other words, the magnetic properties of the powder core 10 can be improved. Thus, a powder core 10 with higher performance can be realized.
[0067] Also, for example, the first resin may be a silicone resin, and the second resin may be an epoxy resin.
[0068] According to this, the above-mentioned powder magnetic core 10 can be realized by using a silicone resin as the first resin and an epoxy resin as the second resin. Furthermore, due to the high strength property of the epoxy resin, the strength of the powder magnetic core 10 can be improved. Therefore, a powder magnetic core 10 with higher performance can be realized.
[0069] Also, for example, the area occupancy rate of the second resin in the cross section of the powder magnetic core may be greater than 0.0% and not more than 20%.
[0070] This makes it possible to form powder magnetic core 10 containing the second resin at an appropriate content ratio, thereby achieving powder magnetic core 10 with higher performance within an appropriate range of the second resin content.
[0071] Also, for example, the area ratio of the second resin to the first resin in the cross section of the powder magnetic core may be greater than 0.0 and less than 0.9.
[0072] This makes it possible to form powder magnetic core 10 containing the second resin at an appropriate area ratio, thereby achieving powder magnetic core 10 with higher performance within an appropriate range of the area ratio of the second resin.
[0073] (Other embodiments, etc.) Although the powder magnetic cores according to the embodiments and the like of the present disclosure have been described above, the present disclosure is not limited to these embodiments.
[0074] For example, the present invention also includes coil components using the above-mentioned magnetic materials. Examples of coil components include inductance components such as high-frequency reactors, inductors, and transformers. In addition, the present invention also includes power supply devices equipped with the above-mentioned coil components.
[0075] Furthermore, the present disclosure is not limited to the embodiment. As long as it does not deviate from the gist of the present disclosure, various modifications conceived by a person skilled in the art to the present embodiment and forms constructed by combining components in different embodiments may also be included within the scope of one or more aspects. [Industrial Applicability]
[0076] The magnetic material according to the present disclosure can be used as a material for the magnetic cores of high-frequency inductors and transformers. [Explanation of symbols]
[0077] 10 powder magnetic core 11 Metal magnetic powder 20, 30 Lead section 25 First terminal member 35 Second terminal member 40 Coil material 100 Electrical Parts
Claims
1. A metal magnetic powder is prepared. A first resin, which is a silicone resin that is liquid at room temperature, is added to the metal magnetic powder in a state where the first resin is dissolved in a solvent in advance, and mixed to cover the metal magnetic powder with the first resin. Then, A second resin, which is an epoxy resin in a liquid state at room temperature, is added to the mixture of the metal magnetic powder and the dissolved first resin in a state of being dissolved in a solvent in advance, and mixed; a mixture of the metal magnetic powder, the first resin, and the second resin is heated to evaporate the solvent, thereby forming a composite magnetic material; The composite magnetic material is put into a mold and pressure-molded, The obtained molded body is heat-treated to cause the second resin to be interspersed in the first resin and to be thermally cured; The second resin has a content, expressed by weight percentage, equal to or less than that of the first resin. A method for manufacturing a powder magnetic core.
2. The area occupancy rate of the second resin in a cross section of the powder magnetic core is greater than 0.0% and not more than 20%. A method for producing the powder magnetic core according to claim 1 .
3. An area ratio of the second resin to the first resin in a cross section of the powder magnetic core is greater than 0.0 and less than 0.
9. The method for producing the powder magnetic core according to claim 1 or 2.
Citation Information
Patent Citations
Powder compact and its producing method, and iron powder used for it
JP2001342501A
Composite magnetic body, and magnetic element and method of manufacturing the same
US20020097124A1